Brand Preference of Men’s Wear - A Case Study - Lalitha, A.; Kumar, J. Ravi; Padmavalli, K. (Indian Journal of Marketing, 2008)
Brand management holds the key in the modern markets, particularly in Indian markets, because Indians are very traditional. India’s traditional dress is Dhoti but gradually, people transmitted into tailor made dresses. Due to the globalization process, Indians are getting attracted to readymade dresses, particularly multinational brands. In the world where products are available with almost similar features like name (with some letters change), package, color of package etc., management of brands is critical for the survival of the products, as well as the companies making them and it is difficult to select the product by the customers.